The Oxford 3D thermophysical model with application to PROSPECT/Luna 27 study landing sites. (March 2020) - King, Oliver; Warren, Tristram; Bowles, Neil; Sefton-Nash, Elliot; Fisackerly, Richard; Trautner, Roland
Abstract: A 3D thermal model that includes a discrete subsurface exponential density profile, surface shadowing and scattering effects has been developed to simulate surface and subsurface temperatures across the Moon. Comparisons of the modelled surface temperatures with the Lunar Reconnaissance Orbiter's Diviner Lunar Radiometer Experiment ("Diviner") measured temperatures show significant improvements in model accuracy from the inclusion of shadowing and scattering effects, with model errors reduced from 10 K to 2 K for mid-latitude craters. The 3D thermal model is used to investigate ice stability at potential landing sites near the lunar south pole, studied for Roscosmos' 'Luna Resource' (Luna 27) lander mission on which the ESA PROSPECT payload is planned to fly. Water ice is assumed to be stable for long periods of time (>1 Gyr) if temperatures remain below 112 K over diurnal and seasonal cycles. Simulations suggest ice can be stable at the surface in regions near to potential landing sites in permanently shaded regions and can be stable below the surface in partly shaded regions such as pole-facing slopes. The simulated minimum constant subsurface temperature (where the seasonal temperature cycle is attenuated) typically occurs at a depth of 50 cm and therefore the minimum depth where ice can be stable is 0 ≤ z ≲ 50 c m . Highlights: 3D thermal model free to download with non-lambertian scattering. Polar lunar water-ice predicted to be stable at shallow depths <50 cm. Landing site accuracy very important for Luna27/PROSPECT mission. Trade-off between illumination fraction and volatile stability for Luna27.